2016
DOI: 10.5935/1806-6690.20160084
|View full text |Cite
|
Sign up to set email alerts
|

Microclimate, development and productivity of robusta coffee shaded by rubber trees and at full sun

Abstract: RESUMO-A importância econômica do mogno ressalta a relevância da análise do vigor de suas sementes visando à formação de mudas com qualidade. O objetivo foi avaliar a influência de diferentes temperaturas e períodos de exposição do teste de envelhecimento acelerado em sementes de mogno. As variáveis analisadas foram: teor de água, emergência de plântulas, índice de velocidade de emergência, freqüência relativa e tempo médio de emergência após o envelhecimento acelerado [(39; 41; 43 e 45 C, durante zero (testem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 22 publications
4
30
0
Order By: Relevance
“…Leaf area is considered one of the main plant response variables to the amount of solar radiation. In the present study, leaf area was higher under shade for the three studied genotypes, which agrees with previous reports for robusta coffee (PARTELLI et al, 2014;ARAÚJO et al, 2016;OLIOSI et al, 2016). Normally, plants respond to changing light conditions by adjusting a suite of morphological and physiological traits (LIU et al, 2016), mainly the leaf area.…”
Section: Figuresupporting
confidence: 92%
See 2 more Smart Citations
“…Leaf area is considered one of the main plant response variables to the amount of solar radiation. In the present study, leaf area was higher under shade for the three studied genotypes, which agrees with previous reports for robusta coffee (PARTELLI et al, 2014;ARAÚJO et al, 2016;OLIOSI et al, 2016). Normally, plants respond to changing light conditions by adjusting a suite of morphological and physiological traits (LIU et al, 2016), mainly the leaf area.…”
Section: Figuresupporting
confidence: 92%
“…Haggar et al (2011), studied shading of arabica coffee in Central America in both conventional and organic management systems and observed that the cumulative yield for the first six years was significantly higher for coffee grown under full sunlight than under shade under conventional management in Costa Rica but that the cumulative coffee yield over five years under full sunlight in Nicaragua was only significantly higher than two of the four shade levels tested. In robusta coffee, Araújo et al (2016) verified the reduction of yield, but, only in the treatment with dense shading. This higher coffee productivity under full sunlight may be explained by the higher degree of floral initiation under these conditions and the inability to remove fruits naturally, which, combined with the sink strength of the seed endosperm, promotes the depletion of plant reserves.…”
Section: Productive Parameters and Grain Yieldmentioning
confidence: 88%
See 1 more Smart Citation
“…In high-altitude broadleaved forests, coffee flourishes under mild understory conditions (Wrigley, 1988). Coffee was brought to Brazil in 1727, and as early as 1731, there were reports of the first exports of coffee have been found with shade tree intercropping in coffee plantations, such as: increased air humidity (Araújo, Partelli, Oliosi, & Pezzopane, 2016;Partelli et al, 2014); increased soil organic matter (Melloni et al, 2018); lower soil density, penetration resistance, and higher total porosity, microporosity, and soil water content (Souza et al, 2017); decreased nutrient leaching, improved soil fertility, and reduced fertilizer requirements (Babbar & Zak, 1995;Cuenca, Aranguren, & Herrera, 1983;Fassbender, 1987;Jaramillo-Botero et al, 2010); reduced incidence of Cercospora coffeicola (Berkeley & Cooke;Salgado, Macedo, Carvalho, Salgado, & Venturin, 2007), Leucoptera coffeella (Guérin-Mèneville & Perrottet; Teodoro, Klein, Reis, & Tscharntke, 2009), several species of fruit flies (Diptera: Tephritoidea; Aguiar-Menezes et al, 2007), and weeds (Concenço et al, 2014;Silva, Perdoná, Soratto, & Negrisoli, 2013); as well as improvement in the quality of the harvested coffee beans (Vaast, Bertrand, Perriot, Guyot, & Génard, 2006). On the other hand, the following disadvantages can be noted: lower soil moisture in the dry season (Coelho, Matsumoto, Lemos, & Souza, 2010;Neves, Martinez, Souza, & Cecon, 2007), higher incidence of Hypothenemus hampei (Ferrari; Wrigley, 1988), need for pruning to regulate shading provided by trees to coffee plants, and, mainly, limitation of coffee production potential and mechanized cultural practices, especially mechanized coffee harvesting (Perdoná & Soratto, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Although, weather conditions (at the regional level) were the same for the two areas, the occurrence of CLM was markedly different (Figure 1 and 2), probably due to the microclimatic effects that the intercropped plants (MORAIS et al, 2006) or shaded trees (ARAÚJO et al, 2016) caused in each coffee planting.…”
Section: Resultsmentioning
confidence: 98%